105k views
5 votes
-3(3+x)+4(x-6)=-4 Please help me with this question

User Delirium
by
5.1k points

1 Answer

6 votes

Answer:


\boxed{ \bold{ \huge{ \sf{x = 29}}}}

Explanation:


\sf{ - 3(3 + x) + 4(x - 6) = - 4 }

Distribute -3 through the parentheses

Similarly, Distribute 4 through the parentheses


\sf{ - 9 - 3x + 4x - 24 = - 4}

Collect like terms


\sf{x - 9 - 24 = - 4}

Calculate


\sf{x - 33 = - 4}

Move 33 to right hand side and change it's sign


\sf{x = - 4 + 33}

Calculate


\sf{x = 29}

Hope I helped!

Best regards!!

User Shubham Khatri
by
5.9k points